2007
DOI: 10.1111/j.1538-7836.2007.02774.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ‘B‐b’ knob‐hole interactions in fibrin binding to adsorbed fibrinogen

Abstract: Summary. Background: The formation of a fibrin clot is supported by multiple interactions, including those between polymerization knobs ÔAÕ and ÔBÕ exposed by thrombin cleavage and polymerization holes ÔaÕ and ÔbÕ present in fibrinogen and fibrin. Although structural studies have defined the ÔA-aÕ and ÔB-bÕ interactions in part, it has not been possible to measure the affinities of individual knob-hole interactions in the absence of the other interactions occurring in fibrin. Objectives: We designed experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
1
21
0
1
Order By: Relevance
“…38 The investigators reported K D s of 5.8M and 3.7M for desA-NDSK and desAB-NDSK, respectively. The slightly higher affinity of desAB-NDSK was attributed to B:b interactions because coinjection of knob B peptides with desA-NDSK or desAB-NDSK hindered only the desAB-NDSK interaction with fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The investigators reported K D s of 5.8M and 3.7M for desA-NDSK and desAB-NDSK, respectively. The slightly higher affinity of desAB-NDSK was attributed to B:b interactions because coinjection of knob B peptides with desA-NDSK or desAB-NDSK hindered only the desAB-NDSK interaction with fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…The slightly higher affinity of desAB-NDSK was attributed to B:b interactions because coinjection of knob B peptides with desA-NDSK or desAB-NDSK hindered only the desAB-NDSK interaction with fibrinogen. 38 Even though this elegant study established the presence of B:b binding interactions, these SPR experiments were performed under equilibrium conditions (ie, low flow rates) and determined only a single equilibrium binding constant. 26 Nonetheless, dynamic off-rates of desA-NDSK (8.6 ϫ 10 Ϫ4 s Ϫ1 ) and desAB-NDSK (1.35 ϫ 10 Ϫ3 s Ϫ1 ) from fibrinogen have been calculated from bond-strength measurements recorded with laser tweezers-based force spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…9 This suggests that in fibrin, the binding site corresponding to knob 'A' is not limited to the GPR sequence and therefore has substantially higher affinity.…”
Section: Knob-hole Interactionsmentioning
confidence: 99%
“…[41][42][43][44] B:b interactions are reported to be exceptionally weak as characterized by high affinity constants and a low strength force to rupture the bonds. 43,45 Prior studies suggest any assembly based on cleavage of FpB alone would be restricted to nonphysiologic conditions of low salt concentrations and low temperatures. 29,39,46 Fib AEK mice and fibrinogen AEK derived from these animals provide novel tools and reagents for more comprehensive studies exploring the consequences of FpA release, FpB release, or both to polymer formation and clot structure both in vitro and in vivo.…”
Section: Arg16cysmentioning
confidence: 99%